Analisis Pengaruh Zakat, Infak dan Shadaqah Terhadap Pertumbuhan Ekonomi di Provinsi Sumatera Utara Periode 2016-2018 (Studi Kasus Baznas Sumatera Utara) - Ade Rahma; Nahar Abdul Ghani; Arifa Pratami (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2020)
This study aims to analyze the influence of Zakat, Infak and Sadaqah on Economic Growth in North Sumatra Province for the period 2016-2018. The variables used in this research are Zakat (X1), Infak and Sadaqah (X2), and Economic growth (Y). The data used in this research is secondary data, the method used is multiple linear regression analysis with the help of SPSS23 to get an overview of the relationship between one variable and another. The results of the study indicate that the zakat variable has a partially significant effect on economic growth. Meanwhile, infak and shadaqah do not have a partially significant effect on economic growth. The results of simultaneous regression analysis show that zakat, infak and shadaqah together affect growth rates.